Cytological features of malignant eccrine acrospiroma presenting as a soft tissue mass axilla: A rare sweat gland tumor with histologic correlation - Pandey, Pinki (Int J Appl Basic Med Res, 2015)
Malignant eccrine acrospiroma is an infrequent, highly malignant primary skin tumor derived from eccrine sweat glands. Though fine-needle aspiration cytology (FNAC) is a well-established diagnostic tool, but if a skin adnexal tumor or primary skin lesion is suspected clinically, the usual approach is biopsy due to easy accessibility. Being itself rare, cytologic features of this lesion is hardly encountered in case reports. As a result, very little is known about the appearance of adnexal tumors like malignant eccrine acrospiroma on fine-needle aspiration samples. A 50-year-old man presented with swelling in the left axilla, clinically suspected to be a soft tissue sarcoma. Fine-needle aspiration was advised, and a cytological diagnosis of malignant eccrine acrospiroma was rendered which was later confirmed on histological examination. Rapid, accurate diagnosis of these tumors is imperative as they have very poor prognosis and an aggressive course with recurrence and/or metastasis. FNAC plays a decisive and easy diagnostic modality in these unusual, rare cases of highly malignant primary skin tumor, and awareness of the lesions is indispensable in their management.